Mast Cell Tumour and Mammary Gland Carcinoma Collision Tumour. Case report and literature review. - Rifici, C; Sfacteria, A; di Giorgio, S; Giambrone, G; Marino, G; Mazzullo, G (Journal of the Hellenic Veterinary Medical Society, 2022)
Collision tumours are the coexistence, at the same venue, of distinct tumours not macroscopically distinguishable and consisting of two independent cell populations without histological admixture. In human medicine, collision tumours in different anatomical sites have been described. In the veterinary literature, few cases exist so far. A 12-year-old female Labrador with a mammary gland nodular lesion was presented for clinical examination. The nodule was surgically removed and underwent histological and immunohistochemical analysis. Histopathological examination revealed two distinct malignant tumours: a mammary gland carcinoma and a cutaneous mast cells tumour. To the author’s knowledge, the paper reports the first case of a collision tumour composed of mammary gland neoplasia and mast cell tumour. The rising interest in collision tumours suggests widening their knowledge and setting up a multimodal approach that includes surgery and targeted therapy.